2022
DOI: 10.3390/fractalfract6070398
|View full text |Cite
|
Sign up to set email alerts
|

On the Lower and Upper Box Dimensions of the Sum of Two Fractal Functions

Abstract: Let f and g be two continuous functions. In the present paper, we put forward a method to calculate the lower and upper Box dimensions of the graph of f+g by classifying all the subsequences tending to zero into different sets. Using this method, we explore the lower and upper Box dimensions of the graph of f+g when the Box dimension of the graph of g is between the lower and upper Box dimensions of the graph of f. In this case, we prove that the upper Box dimension of the graph of f+g is just equal to the upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[17][18][19][20] for more details. More recent work about the fractal dimensions of the graph of continuous functions can be found in [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] for more details. More recent work about the fractal dimensions of the graph of continuous functions can be found in [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This problem can be traced back to the research made first by Falconer [33], who showed that the box dimension of the sum of two continuous functions equals the greater of the box dimensions of them. On this basis, a group of academic workers has pushed this study forward and obtained a series of preliminary conclusions, whose related progress can be found in [34][35][36][37][38][39][40]. So in this paper, we shall focus on the fractal dimension of the superposition of two fractal surfaces and investigate whether it has the same result as that of fractal curves.…”
Section: Introductionmentioning
confidence: 99%